2012
DOI: 10.1002/jcp.23019
|View full text |Cite
|
Sign up to set email alerts
|

Combination of low O2 concentration and mesenchymal stromal cells during culture of cord blood CD34+ cells improves the maintenance and proliferative capacity of hematopoietic stem cells

Abstract: The physiological approach suggests that an environment associating the mesenchymal stromal cells (MSC) and low O(2) concentration would be most favorable for the maintenance of hematopoietic stem cells (HSCs) in course of ex vivo expansion of hematopoietic grafts. To test this hypothesis, we performed a co-culture of cord blood CD34(+) cells with or without MSC in presence of cytokines for 10 days at 20%, 5%, and 1.5% O(2) and assessed the impact on total cells, CD34(+) cells, committed progenitors (colony-fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
36
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(37 citation statements)
references
References 69 publications
1
36
0
Order By: Relevance
“…Hypoxia induces metabolic changes, enhances survival, reduces differentiation and promotes self-renewal of mesenchymal/stromal cells [5456]. Furthermore, co-culture with these cells in hypoxia promotes maintenance and expansion of normal HSCs and human AML cells [39, 56, 57]. Finally, the poorly oxygenated niche and the hypoxia-induced glycololytic metabolism have been linked to chemoresistance in B-ALL, T-ALL, AML, lymphoma and MM cases [5876].…”
Section: Hypoxia In Hms and The Stromal Compartmentmentioning
confidence: 99%
“…Hypoxia induces metabolic changes, enhances survival, reduces differentiation and promotes self-renewal of mesenchymal/stromal cells [5456]. Furthermore, co-culture with these cells in hypoxia promotes maintenance and expansion of normal HSCs and human AML cells [39, 56, 57]. Finally, the poorly oxygenated niche and the hypoxia-induced glycololytic metabolism have been linked to chemoresistance in B-ALL, T-ALL, AML, lymphoma and MM cases [5876].…”
Section: Hypoxia In Hms and The Stromal Compartmentmentioning
confidence: 99%
“…This discovery led to the development of a considerable number of coculture systems for the expansion of HSPCs with various sources of feeder cells including BM-derived stromal cells [37,38], immortalized stromal cells [39][40][41] and endothelial cells [42][43][44][45][46] and bone marrow mesenchymal stem cells (MSC) [47][48][49][50][51][52][53]. Examples of such system are presented in Table 1 along with their principal properties and results.…”
Section: Development Of Coculture Procedures and Cytokine Cocktails Fmentioning
confidence: 99%
“…Examples of such system are presented in Table 1 along with their principal properties and results. The major findings of these studies can be summarized as follow; i) coculture with stromal cells general increases the expansion and/or length of which HSPC proliferate [39,50,54], ii) coculture-expanded HSPCs retain phenotypes associated with primitive primary HSPCs [50,55,56], iii) exogenous cytokines synergize with stromal cells to promote HSPC expansion [49,50,[57][58][59][60][61][62], iv) both contact-dependent and contact-independent activities have been reported which suggest that the regulation of the HSPC compartment by stromal cells is multifaceted in nature [37,55,56,58,[63][64][65][66][67], v) coculture with stromal cells generally improves the engraftment activity of HSPCs vs. those expanded without stromal cells [37,39,[47][48][49][50][51]68], vi) coculture is more effective to promote the expansion of HSPCs from CB mononucleated cells (MNC) than stroma-free cultures [59,69,70] and, vii) M A N U S C R I P T A C C E P T E D ACCEPTED MANUSCRIPT 7 stromal cells secrete a wide array of cytokines and chemokines [49,55,65,[71]…”
Section: Development Of Coculture Procedures and Cytokine Cocktails Fmentioning
confidence: 99%
“…These results support our hypothesis that osteogenic secretory molecules present in the matrices may be responsible for expanding more HSPCs on MX2. However, Hammoud et al [68] have recently demonstrated that association of co-culture and low O 2 concentration induces expansion of committed progenitors and also ensures a better maintenance/expansion of HSPCs, pointing to oxygenation as a physiological regulatory factor but also as a cell engineering tool. The greater expansion of progenitors on matrices grown in higher O 2 conditions is consistent with the concept that the vascular niche promotes expansion of committed progenitors, while the greater expansion of cells with a more primitive phenotype on matrices grown under low O 2 conditions is consistent with the concept that the hypoxic endosteal niche promotes self-renewal [69,70].…”
Section: Discussionmentioning
confidence: 99%